PENGARUH KARAKTERISTIK BUDAYA ORGANISASI, LOCUS OF CONTROL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN STUDI PADA PERUSAHAAN DAERAH PENGELOLA AIR LIMBAH (PD PAL) KOTA BANJARMASIN - Dessy Rosiana; Ahmad Alim Bachri; Maya Sari Dewi (Universitas Lambung Mangkurat, 2016)
This research was aimed to simultaneously analyze the significantly positive effect of organizational culture characteristics, locus of control and work discipline towards employee performance at PD PAL Banjarmasin; also to partially analyze the significantly positive effect of organizational culture characteristics, locus of control, and work discipline towards employee performance at PD PAL Banjarmasin. The type of this research was explanatory research. All population became the samples in this research. The information collection of 53 employees who acted as the respondents in this research was done by using questionnaire arranged in 5 Likert Scale. The data analysis used multiple linear regression analysis, multiple determination coefficient, as well as F test and t test. The result of this research showed that the variable of organizational culture characteristics, locus of control and work discipline simultaneously has a significantly positive effect towards employee performance at PD PAL Banjarmasin. The organizational culture characteristics partially does not have a positive and significant effect towards employee performance. Partially the locus control has a significantly positive effect towards employee performance. Work discipline partially has a significantly positive effect towards employee performance. The implication to the management, based on the result of this research, is (1) the implementation of the organizational culture characteristics needs to be socialized among employee of PD PAL, and (2) a strong control on the locus control and discipline is needed to improve the employee performance.